Genetic Cholestasis: Lessons from the Molecular Physiology of Bile Formation - Peter LM Jansen; Michael Müller (Canadian Journal of Gastroenterology)
Progressive familial intrahepatic cholestasis (PFIC) is a group of severe genetic cholestatic liver diseases of early life. PFIC types 1 and 2 are characterized by cholestasis and a low to normal serum gamma-glutamyltransferase (GGT) activity, whereas in PFIC type 3, the serum GGT activity is elevated. PFIC types 1 and 2 occur due to mutations in loci at chromosome 18 and chromosome 2, respectively. The pathophysiology of PFIC type 1 is not well understood. PFIC types 2 and 3 are caused by transport defects in the liver affecting the hepatobiliary secretion of bile acids and phospholipids, respectively. Benign recurrent intrahepatic cholestasis (BRIC) is linked to a mutation in the same familial intrahepatic cholestasis 1 locus at chromosome 18. Defects of bile acid synthesis may be difficult to differentiate from these transport defects.Intrahepatic cholestasis of pregnancy (ICP) appears to be related to these cholestatic diseases. For example, heterozygosity in families with PFIC type 3 is associated with ICP, but ICP has also been reported in families with BRIC.In Dubin-Johnson syndrome there is no cholestasis; only the hepatobiliary transport of conjugated bilirubin is affected. This, therefore, is a mild disease, and patients have a normal lifespan.